Characteristics of patients with hematologic malignancies without seroconversion post-COVID-19 third vaccine dosing. Issue 1 (14th February 2023) - Hallmeyer, Sigrun; Thompson, Michael A; Fitzpatrick, Veronica; Liao, Yunqi; Mullane, Michael P; Medlin, Stephen C; Copeland, Kenneth; Weese, James L
Abstract: Objectives: The objective of this study is to explore the characteristics of the subset of patients with hematologic malignancies (HMs) who had little to no change in SARS-CoV-2 spike antibody index value levels after a third mRNA vaccine dose (3V) and to compare the cohort of patients who did and did not seroconvert post-3V to get a better understanding of the demographics and potential drivers of serostatus. Study design: This retrospective cohort study analyzed SARS-CoV-2 spike IgG antibody index values pre and post the 3V data on 625 patients diagnosed with HM across a large Midwestern United States healthcare system between 31 October 2019 and 31 January 2022. Methods: To assess the association between individual characteristics and seroconversion status, patients were placed into two groups based on IgG antibody status pre and post the 3V dose, (−/+) and (−/−). Odds ratios were used as measures of association for all categorical variables. Logistic regressions were used to measure the association between HM condition and seroconversion. Results: HM diagnosis was significantly associated with seroconversion status ( P = 0.0003) with patients non-Hodgkin lymphoma six times the odds of not seroconverting compared with multiple myeloma patients ( P = 0.0010). Among the participants who were seronegative prior to 3V, 149 (55.6%) seroconverted after the 3V dose and 119 (44.4%) did not. Conclusion: This study focuses on an important subset of patients with HM who are not seroconverting after the COVID mRNA 3V. This gain in scientific knowledge is needed for clinicians to target and counsel these vulnerable patients.